The Utilization of Electronic Archives as a Support for Study Employee Performance at The Customs and Excise Office Type A Semarang Customs - Tanty Qornia Dewi; Yustina Erti Pravitasmara Dewi (Universitas Pendidikan Ganesha, 2021)
Technological developments make it easier for employees to carry out work, including archive management employees. Archives undergo changes and developments in electronic form. The development of supporting technology for electronic archive management. This study aims to analyze the use of electronic records to support the effectiveness of employee performance and the factors that support employee performance. This qualitative research uses a descriptive approach. The technique used to collect data is interviews. The instrument used to collect data is a questionnaire. This study uses three stages of data analysis, namely data reduction, data presentation, and concluding. The research subject is the selected resource person, an employee with the position of Customs and Excise Inspector. The technique used to analyze the data is descriptive qualitative analysis. The results of this study indicate that the use of electronic archives supports employee performance. The benefits of using electronic archives include easy and fast use, safe, and time-saving. There are four factors supporting employee performance: the work environment, ability, motivation, and adequate facilities. Factors supporting employee performance in using electronic records are leaders who always encourage employees to learn and develop themselves and a comfortable work environment for employees, human resource capabilities, and adequate facilities and equipment provided by the institution.